Determinants of vulnerability of bean growing households to climate variability in Colombia. (13th September 2020) - Perez, Lisset; Rios, David A.; Giraldo, Diana C.; Twyman, Jennifer; Blundo-Canto, Genowefa; Prager, Steven D.; Ramirez-Villegas, Julian
ABSTRACT: Climate variability largely affects agriculture in the developing world where rainfed agriculture is highly prevalent, and farmers rely on favourable climatic conditions to grow their crops. In Colombia, interannual climate variability can increase human vulnerabilities. Evidence on the vulnerability of farming households to climate variability at the local scale is, however, scarce. Here, we assessed the climate vulnerability and its determinants for a representative sample of 567 bean growing households in Santander, Colombia. We first applied Multiple Correspondence Analysis to calculate a vulnerability index and its components (exposure, sensitivity and adaptive capacity). The vulnerability index is in turn used to classify households into three vulnerability groups, namely, high, medium, and low. We then estimated a Generalized Ordered Probit Model to assess the probability of falling into each vulnerability category according to the household and farm management characteristics. We find that vulnerability is highly variable in the study region, with up to 65% of households classified as highly vulnerable. Geography, access to agronomic training, crop diversification, the percentage of household members making productive decisions and the gender of the household head are the most important factors determining the probability of being more or less vulnerable.